Intestinal microbial diversity and functional analysis of Urechis unicinctus from two different habitats: pond polycultured with Penaeus japonicus and coastal zone - Y Tang; S Ma; Y Liu; Y Pi; Y Liu; Y Zhao (Aquaculture Environment Interactions, 2021)
Urechis unicinctus is an important commercial and ecological invertebrate that has potential applications in the study of marine invertebrate evolution and marine pharmaceutical development. Here we analyzed the intestinal microbial diversity of U. unicinctus from 2 different habitats using 16S rDNA 454 high-throughput sequencing. The dominant phyla were Proteobacteria, Bacterioidetes, Firmicutes, and Actinobacteria in gut samples of U. unicinctus, which significantly differed from those in its 2 habitats (i.e. intertidal mudflat and pond polyculture). Exceptions were Proteobacteria, Firmicutes and Bacterioidetes, which were the dominant phyla in the sediment and water samples. The top 15 genera in the gut samples did not show any significant differences between the 2 habitats. Functional analysis of the intestinal microbial community showed that metabolism, including carbohydrate and amino acid metabolism, was the most important function. Methane metabolism was one of the main components of energy metabolism. The gut microbes also played an important role in environmental and genetic information processing, cellular processes, etc. These findings provide an understanding of gut microbiome composition and diversity in U. unicinctus from 2 different habitats. Our results can inform the management of animal health in U. unicinctus farming activities and further gut microecology research.